2015
DOI: 10.21273/jashs.140.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Target Gene Hsp70 and Membrane Stability Determine Heat Tolerance in Chili Pepper

Abstract: Experiments were carried out to study the mechanisms for heat tolerance in chili pepper (Capsicum annuum). To assess these mechanisms, six genotypes were evaluated for cellular membrane thermostability (CMT) and for HSP70 gene expression. The plants were grown in an experimental plant growth chamber. The mean value of CMT indicates that membrane integrity was not damaged by the high temperature treatment (50 °C) in most of the genotypes. The genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…In addition, in vitro heat treatment pollination success rate was also significantly correlated with pollination success rate during the winter season, which seems contradictory but could be explained by certain accessions having generally higher or lower pollination success rates, despite the growing season or heat treatment. For example, AVPP9905, a previously reported heat-tolerant line [34], was among the samples with the highest average pollination success rates when used as a male parent during the summer season (26%), the winter season (54%), under in vitro heat treatment (33%), and under no treatment (47%), while AVPP9823 was among the samples with the lowest average pollination success rates during the summer season (15%), the winter season (44%), under in vitro heat treatment (20%), and under no treatment (39%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vitro heat treatment pollination success rate was also significantly correlated with pollination success rate during the winter season, which seems contradictory but could be explained by certain accessions having generally higher or lower pollination success rates, despite the growing season or heat treatment. For example, AVPP9905, a previously reported heat-tolerant line [34], was among the samples with the highest average pollination success rates when used as a male parent during the summer season (26%), the winter season (54%), under in vitro heat treatment (33%), and under no treatment (47%), while AVPP9823 was among the samples with the lowest average pollination success rates during the summer season (15%), the winter season (44%), under in vitro heat treatment (20%), and under no treatment (39%).…”
Section: Discussionmentioning
confidence: 99%
“…The response of chile pepper to high temperatures at the vegetative (generally seedling) [34,[39][40][41][42][43] and reproductive [23,24,26,44,45] stages during the growing season has been previously explored. In recent years, researchers have characterized differentially expressed genes in response to high-temperature stress in chile pepper [34,[39][40][41][42]. In vitro bioassays have been developed to effectively screen chile pepper accessions for heat tolerance [17,18,21].…”
Section: Discussionmentioning
confidence: 99%
“…In their simplest form the genes that underlie these traits show low expression in the absence of stress but turn on when the plant senses environmental change. For instance, certain heat shock proteins are produced above only a certain temperature (170). Most stress responses that we have described fall into this category, though their associated costs vary.…”
Section: Induced Versus Constitutive Responses and Trade-offsmentioning
confidence: 99%
“…Especially, as an essential regulator of protein, the Hsp70 has the tendency to maintain internal cell stability, protecting the injured organisms by enhancing the stability of mRNA and translating preferentially under heat condition (McGarry and Lindquist, 1985). Previous studies showed that overexpression of Hsp70 gene was leading to increasing the tolerance of Arabidopsis thaliana (Shinya et al, 2014), Capsicum annuum (Guo et al, 2014;Usman et al, 2015), Zea mays (Ristic et al, 1991), and O. sativa (Wang et al, 2014) under heat and drought stress.…”
Section: Introductionmentioning
confidence: 99%